Reactive mass transport in concrete including for gaseous constituents using a two-phase moisture transport approach. (30th January 2020) - Addassi, Mouadh; Johannesson, Björn
Highlights: Reactive mass transport model including for gas transport as a separate phase. Durability estimation of cement-based materials. The effect of combined altering mechanism in unsaturated conditions. Comparing numerical simulation examples to literature findings. Abstract: This article presents the further development of a tool for multi-phase reactive mass transport modeling for durability estimation of cement-based materials, by the addition of the gas phase, adopting a truly separate two-phase moisture transport approach. The governing system of equations are based on physically sound hybrid mixture based version of the Poisson-Nernst-Planck system of equations including gaseous transport in the air-filled space, ionic transport in the liquid phase, electro-migration of ionic species, a two-phase moisture transport model, and sorption. The addition of the gas phase and the two-phase moisture description enables the user of the model to investigate individual and combined effects of different degradation processes in unsaturated systems. The altering of hydrated cement under three different environments were studied representing an accelerated carbonation environment, a submerged marine environment and a cyclic drying-wetting zone in a marine environment, to illustrate some of the model's capabilities.